دور التسهيلات الائتمانية الممنوحة من قبل المصارف التجارية في تحقيق النمو الاقتصادي في فلسطين: دراسة قياسية للفترة 1994-2013 - أبو عيدة، عمر محمود; زبدة، خالد حسن Zebda, Khaled Hassan (جامعة الخليل, 2015)
يهدف هذا البحث إلى تحليل مدى مساهمة المصارف التجارية في تحقيق النمو الاقتصادي من خلال ما تقدمه من تسهيلات ائتمانية للقطاعات الاقتصادية المختلفة خلال الفترة (1994-2013). ولتحقيق هذا الهدف تم اقتراح نموذج قياسي مكون يعتمد على تحليل الانحدار المتعدد لمعرفة أثر التسهيلات الائتمانية على نمو الناتج المحلي الإجمالي الحقيقي، ومن أجل أن يتناسب التحليل مع واقع الظروف التي يمر بها الاقتصاد الفلسطيني تم تقسيم فترة الدراسة إلى أربع فترات مختلفة. ومن أهم النتائج التي توصل إليها البحث وجود علاقة طردية بين التسهيلات الائتمانية الممنوحة من قبل المصارف التجارية والناتج المحلي الإجمالي حيث بلغ الأثر (0.10) للفترة (1994-2000)،و (0.001) للفترة (2001-2005)، و(0.37) للفترة (2006-2013) و0.05% على طول الفترة (1994-2013). ومن أهم التوصيات التي تم اقتراحها ضرورة قيام سلطة النقد الفلسطينية بتعزيز سياستها النقدية بشكل يؤدي إلى تنظيم الجهاز المصرفي الفلسطيني لما لذلك من أهمية قد تعود على عمل المصارف التجارية في تجميع المدخرات ومنح التمويل اللازم للقطاعات الاقتصادية المختلفة ودعم مسيرة النمو الاقتصادي الفلسطيني.
The aim of this research is to analyze the role of commercial banks which is presented by the volume of credit with regard to economic growth in Palestine both from the productive sectors point of view and from the Gross Domestic Product point of view during the period of (1994- 2013). In order to achieve such aim an econometric model has been adopted based on Cob-Douglas production function in which the impact of total banks credit granted to the economy on the economic growth in Palestine has been tested. The empirical results of the model showed appositive relationship between commercial banks credit and the economic growth in Palestine in which the impact was 0.10% during the period of (1994-2000), and 0.001% during (2000-2005), and 0.37% during the period of (2006 2013), and 05% during the period of (1994-2013). In the light of the above results many recommendations were suggested among them the most important one was addressed to the Palestinian Monetary Authority to pay more emphasis on its monetary policy to increase the capability of the commercial banks in collecting the savings of the society and financing the economic activities which have a vital role on the economic growth of the Palestinian economy as a whole.
Keywords: البنوك التجارية -- الأئتمان المصرفي -- التنمية الاقتصادية -- فلسطين